Neonatal Heart Responds to Pressure Overload With Differential Alterations in Various Cardiomyocyte Maturation Programs That Accommodate Simultaneous Hypertrophy and Hyperplasia - Ding, Xiaoning; Wang, Shoubao; Wang, Ye; Yang, Junjie; Bao, Nan; Liu, Jinfen; Zhang, Zhen (Frontiers in Cell and Developmental Biology, 2020)
Pressure overload is one of the pathophysiological conditions commonly associated with right-sided congenital heart disease (CHD). Patients suffer from this condition right after birth. However, little is known about how neonatal heart reacts to it. We have previously established a pulmonary artery banding (PAB) model on neonatal rat. Here we show that PAB accelerated transition of mononuclear cardiomyocytes into multinucleated cells to promote hypertrophic growth in neonatal heart. The elevated afterload significantly increased the mitotic activities of neonatal cardiomyocytes. Consistent with the proliferative potential of neonatal cardiomyocytes, the elevated pressure overload also increased mitotic and cytokinetic marker counts of cardiomyocytes. Using cardiomyocyte-specific lineage tracing, we noticed a clonal expansion of rare unlabeled cardiomyocytes in the PAB group, revealing a subgroup of cardiomyocytes with a strong capability of proliferation. In addition, PAB hearts didn’t have the accumulation of macrophages, which is an immune response essential for neonatal heart regeneration in injury models. Transcriptomic analyses revealed that neonatal PAB induced an expression profile featuring both cardiomyocyte hypertrophy, such as highly activated translation, oxidative phosphorylation, and mitochondrial biogenesis programs etc., and immature cardiomyocyte, such as enhanced cell cycle activities and glycolytic metabolism, down-regulated cytoskeleton and ion channel gene expression, and maintenance of fetal-specific sarcomeric isoforms etc.. It indicates that pressure overload has differential impacts on various cardiomyocyte maturation (CM) programs that may contribute to the concurrent cardiomyocyte hypertrophy and hyperplasia. The bivalent cellular status highlights the plasticity of neonatal cardiomyocytes that can be exploited to adapt the postnatal environment.